Marginal men, respectable masculinity and access to HIV services through intimate relationships with female sex workers in Kampala, Uganda. (March 2022) - Mbonye, Martin; Siu, Godfrey; Seeley, Janet
Abstract: Masculinity influences men's sexual risk-taking behaviour and affects uptake of HIV services. We draw on data from a year-long (2019) ethnographic study focusing on men in relationships with female sex workers (FSW) in Kampala, Uganda to examine how and why two marginalised groups of people may interact to produce positive health behaviours. Data from in-depth interviews, focus group discussions and participant observation were collected and analysed. We discuss three main themes; the first of which focuses on marginalised masculinities and HIV risk. In this theme we show how accounts of men's life trajectories portrayed a remarkably similar pattern of early deprivation of opportunities and how this shaped construction of risky masculinities. The second theme describes men's relationships with FSW and how this facilitated access to HIV services. We discuss how very marginal women (FSWs) help very marginal men adopt more positive health behaviours. We show how threats to masculinities arising from sex work stigma, men's failure to have exclusive sexual rights over their FSW partner, and men's economic disadvantage are negotiated and dealt with to create an enabling environment for men's uptake of HIV services. The final theme focuses on the positive and negative practices of the men after engaging with HIV services. We conclude that the two marginalised groups can mobilise and combine new aspirations to produce positive health behaviours manifested through FSW assisting their male partners to access HIV services. We suggest that this perspective opens up new opportunities for engaging with marginalised groups and tackling the problem of high HIV infection among key populations. Highlights: Female sex workers can be agents of positive health change for their male partners. Marginalised men can re-establish their masculinity through their relationship. Marginalised by her sex work, a woman can gain security with her long-term partner. Men's uptake of HIV services can be improved through these relationships.